Deskripsi Penyalahgunaan Narkoba dan Merokok pada Siswa SMA dan SMK di Kota Purwokerto Kabupaten Banyumas - Wahyudi Mulyaningrat; Keksi Girindra Swasti (Journal of Bionursing, 2022)
The background of this research: at present, the phenomenon of drug abuse in Indonesia is very alarming. The spread of illegal drugs penetrated various regions. Smoking is the gateway for drug entry in adolescents. This study aims to determine how the description of drug abuse and smoking among adolescents, namely in high school and vocational students in Purwokerto, Banyumas Regency. Research use survey methods and analyzed by descriptive statistics. The results of this study are in the category of knowledge about smoking there are 56 students (53.8%) are moderate and 48 students (46.2%) good. In the category of knowledge about drugs, there is 1 student (1.0%) poor, 24 students (23.1%) moderate, and 79 students (76.0%) good. The results in the attitude about the smoking category were 33 students (31.7%) poor, 52 students (50.0%) moderate, and 19 students (18.3%) good. In the category of attitude about drug abuse, there are 29 students (27.9%) bad, 49 students (47.1%) moderate, and 26 students (25.0%) good. These results indicate that the description of knowledge and attitudes towards drug abuse and smoking among high school and vocational students still needs handling seriously.